Evaluasi Kinerja PLTS On-Grid 600 kWp pada Jaringan Distribusi Gili Trawangan - Rifky Irawan; Fransisco Danang Wijaya; Adha Imam Cahyadi (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2024)
Indonesia is one of the countries that remains reliant on the utilization of fossil energy. The increasing demand for fossil energy is causing a decrease in the availability of fossil energy, consequently leading to an increase in fossil fuel prices. Therefore, one of the efforts that can be undertaken involves establishing new renewable energy (NRE) plants to diminish reliance on the use of fossil-fueled plants. One of the NRE plants built by the government is the 600 kWp Gili Trawangan On-Grid solar power plant. After ten years of operation, an evaluation of the 600 kWp Gili Trawangan On-Grid solar plant is necessary to assess its performance in meeting electricity load requirements. The power and electrical energy generated by a solar power plant can be evaluated by comparing its current power and energy production with the potential power and energy that should be generated. To determine the current power and energy production generated by the solar power plant, the measurement results from the PLN. Additionally, to ascertain the potential power and energy that the solar power plant should be capable of producing at this time, simulation results from Homer software were employed. The results demonstrate that the power and energy measured by PLN are lower than the potential power and energy that should be achievable using Homer software for solar power plants. According to PLN measurement, the average power production and energy were 196.72 kW and 765.92 kWh, respectively. Meanwhile, based on the simulation results were 207.10 kW and 840.39 kWh.